Komunikasi Pariwisata Berdasarkan Analisis Sektor Wisata di Kabupaten Bandung Barat - Setiaputri, Maharani Dewanti (Jurnal Ilmiah Wahana Pendidikan, 2024)
West Bandung regency has many attractions that can be visited by tourists. In increasing tourist visits, KBB implemented various marketing through traditionally and online methods. In order to determine originality and distinguish with previous research, researchers conducted a study at the West Bandung Tourism and Culture Office in the Era of the Covid-19 Pandemic, where the tourism sector experienced a very significant decrease in visitor numbers. Some methods are used in gathering information with depth interview methods, empirical descriptive and SWOT analysis. The purpose of this study is to find out and analyze Tourism Communication through tourism marketing mix strategies used by Department of Tourism and Culture Province in West Bandung Regency in increasing tourist visits. Also, to find out the challenges and solutions in promoting West Bandung Regency Tourism (especially the impact of the decrease in tourist numbers due to the Covid-19 pandemic). Therefore, this study will look at marketing analysis before pandemics - during pandemics - after Community Activities Restrictions Enforcement has been lifted.